Performances of improved and traditional rice based jhum cultivation in a hill district of Bangladesh - Mahmud, Sujan; Alam, Md Rashidul; Amin, Mohammed; Hassan, Md Mahmudul (Journal of the Bangladesh Agricultural University, 2018)
Jhum is a customary farming which is very important for the livelihood of the alpine people of Bangladesh. Total productivity of the traditional practice of jhum cultivation is very low. The study was conducted to identify the yield gap between improved and local practices in Bandarban district of Bangladesh during March to September; 2017.The experiment was laid out in randomized complete block design (RCBD) with ten replications. Improved jhum practice produced the higher yields of rice (3113kg/ha), seed cotton (456 kg/ha), sesame (478 kg/ha) and maize (627 kg/ha) than traditional local jhum. Rice Equivalent Yield (REY) was also higher (40.23%) in improved jhum (6786.8kg/ha) than local jhum (4339.8 kg/ha). Improved jhum’s rate of returns (2.15) was higher than traditional jhum’s rate of returns (1.56). Improved practice in jhum cultivation increased yield and it was economically profitable over traditional practice. J. Bangladesh Agril. Univ. 16(2): 193-197, August 2018